Correlates and disparities of intention to vaccinate against COVID-19. (March 2021) - Callaghan, Timothy; Moghtaderi, Ali; Lueck, Jennifer A.; Hotez, Peter; Strych, Ulrich; Dor, Avi; Fowler, Erika Franklin; Motta, Matthew
Highlights: More than 30% of the US public does not intend to vaccinate against COVID-19. Intention to refuse vaccination is highest for women and Blacks. COVID-19 vaccine refusal is most often due to safety and effectiveness concerns.